Arduino Implementation for Development Digital Capacitance Meters as Laboratory Measurement Devices - Denny Hardiyanto; Prabakti Endramawan; Ridho Nur Taufiqul Manan; Dyah Anggun Sartika (Politeknik Ganesha Medan, 2022)
Electronics Practicum in the Laboratory is a routine activity carried out to support student skills. Capacitors are one of the components that are often used in practice. Capacitors are one of the passive electronic components that have a magnitude value in the form of capacitance in Farad units. The capacitance value indicates the capacitor's ability to store electric charge. However, the value contained on the capacitor label is not necessarily the actual value because the capacitor has a tolerance range. Of course, this is very influential in the measurement and performance of electronic circuits that use capacitors. In addition, another factor that supports this research is that the available measuring instruments, such as the multimeter, are not yet equipped with capacitance measurements. Capacitance meters available in the market are still analog. The purpose of this study is to design a device that can measure the capacitance value of capacitors as a measurement device in a digital laboratory, namely the Digital Capacitance Meter. This device is made using Arduino Uno as a microprocessor for data processing. The method used is to apply the process of charging and discharging the capacitor. In this case, Arduino Uno activates a timer to measure the time required to charge and discharge the capacitor so that the Time Constant value is obtained. By using the formula T = 0.693RC, the capacitance value can be obtained. In testing using 3 different capacitors and 10 times testing on each capacitor, the accuracy of the device is 97.76% and a relative error of 2.24%.